PREPARING STUDENTS FOR METHODOLOGICAL TRAINING BASED ON PEDAGOGICAL TECHNOLOGIES AND INNOVATIVE METHODS - Abdullayeva Gavhar Ro’zimurod qizi (The Conference Hub, 2025)
This paper explores the role of pedagogical technologies and innovative teaching methods in enhancing students’ methodological training. Emphasis is placed on integrating theoretical and practical knowledge, improving education quality, and promoting personalized and interactive learning. The study highlights various modern approaches, including digital education, problem-based learning, gamification, and project-based learning, which contribute to developing students’ critical thinking, creativity, and practical skills. The article suggests that effective implementation of these methods can significantly improve the quality and effectiveness of the educational process.
Keywords: pedagogical technologies, methodological training, innovative teaching methods, interactive learning, project-based learning, digital education, personalized learning